Sabah village food restaurant / Jhonson Sintia… [et al.] - Sintia, Jhonson; Sabli, Norazidah; Magik, Mohd Ali; Madi, Siti Farhanah; Jinurahim, Nor Fadziela (Faculty of Business Management, Universiti Teknologi MARA, 2013)
Our company the Sabah village Food Restaurant was focus on provide and serve food and beverages to the customers, our company was only providing Sabah local food, compare to the other restaurant, because the other restaurant was serving many variety origins of their food. We focus to only serve Sabah village food or local food because we want to maintain the unique preparation of local food in Sabah, and also to able to introduce it to the other people from outside of this state. Next is, the name of our company Sabah village Food Restaurant was based our focus on food and beverages where we only serve Sabah local food, so we came up with the idea to make the company name to Sabah Village Food Restaurant. This business was partnership business, where we distribute our position to General Manager, Marketing Manager, Financial Manager, Operation Manager, and lastly, we have Administration Manager. And we only operate our business six days in a week.